2011
DOI: 10.1007/s11845-011-0675-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ozone therapy and coenzyme Q10 combination on oxidative stress markers in healthy subjects

Abstract: The results of this study reveal the beneficial effects of ozone therapy + coenzyme Q(10) combination in prevention of oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 23 publications
0
33
0
1
Order By: Relevance
“…The main benefits of ozone therapy on humans are: the antibiotic effect and static effect on viruses, [1][2][3][4] activation of the mitochondrial antioxidant system, [5][6][7] increased adenosine triphosphate (ATP) production, hemorheological effect with greater activity of the oxygen-carbon dioxide exchange in red blood cells, 8 and anti-inflammatory action. 9 In addition, there is reactivation of the cerebral microcirculation and metabolism, 7 an anti-ischemic protective effect, [10][11][12] antithrombotic effect, 13 and anti-tumor action.…”
Section: Introductionmentioning
confidence: 99%
“…The main benefits of ozone therapy on humans are: the antibiotic effect and static effect on viruses, [1][2][3][4] activation of the mitochondrial antioxidant system, [5][6][7] increased adenosine triphosphate (ATP) production, hemorheological effect with greater activity of the oxygen-carbon dioxide exchange in red blood cells, 8 and anti-inflammatory action. 9 In addition, there is reactivation of the cerebral microcirculation and metabolism, 7 an anti-ischemic protective effect, [10][11][12] antithrombotic effect, 13 and anti-tumor action.…”
Section: Introductionmentioning
confidence: 99%
“…antioxidant systems (8,9). Furthermore, it has been reported that ozone oxidative preconditioning (OOP), a type of ozone therapy (10) has a protective effect against IRI in the liver and kidney (11,12).…”
Section: Effect Of Ozone Oxidative Preconditioning On Oxidative Stresmentioning
confidence: 99%
“…Some report has showed that ozone had numerous abilities, ozone therapy could be used to treat infected wound and empyrosis 1 . Furthermore, researches have showed that ozone therapy could enhance the function of anti-oxidative system, which could mitigate the damage coused by oxidative stress 2,3 . However, to our knowledge, the effect of ozone oxidative preconditioning on inflammation and oxidative stress injury in the homologous kidney transplantation has not been studied up till now.…”
Section: ■ Introductionmentioning
confidence: 99%